Scope of Forage and Fodder Production in the North-eastern State of Tripura, India - Dey, Joy Kumar; Kumar, Basant (International Journal of Economic Plants, 2017)
Tripura has a large livestock population-a resource that provides livelihood opportunity an employment to over 75% of rural people. In, Tripura different types of forage and fodder crops are grown for the managing livestock feed demands; some of the important fodder crops grown are fodder maize, cowpea, oat, fodder sorghum etc. The shrinking land base and natural resource degradation restricts grazing, forage and fodder availability. In India fodder sub-sector of Agriculture sector’s direction for future is vague in nature. Though Government of India through various cells like IGFRI, Fodder cell in animal husbandry department taking innumerable initiatives to change the fodder management status in India. But this organizing effort is not effective enough to change the conditions comparing to other developed countries. The strategies for bridging the gaps in demand and supply of feeds and fodder crops are discussed in relation to the available niches. It is possible to meet the challenge with all round development in the area of fodder, grassland and crop residue production improvement. Hence, this case study is a special attempt to recognize the Indian as well as Tripura Fodder Industry as Public and Private Sector Myopia or vision. This study is mainly based on the secondary data collected from the various sources like published report of Government of India, Government of Tripura, Web Articles, Journals, research report.